The Significance of Right Speech in Theravada Buddhism and its Importance in the Present Day Context - Barua, Neeru (Social Science Review, 2023)
The highest importance is given to right speech in Buddhism. It plays a vital role in the present day context. There are enormous examples of speech to inflame violence and make separation among the people and even the world communities. It is hard to find out the path of peace and harmony among the society. Right speech can contribute significantly to building a harmonious and sustainable society to achieve SDG’s. Social Science Review, Vol. 40(1), Jun 2023 Page 151-163